Search for direct pair production of the top squark in all-hadronic final states in proton-proton collisions at s√=8 TeV with the ATLAS detector - Onofre, A. (2014)
The results of a search for direct pair production of the scalar partner to the top quark using an integrated luminosity of 20.1 fb−1 of proton-proton collision data at s√ = 8 TeV recorded with the ATLAS detector at the LHC are reported. The top squark is assumed to decay via t¯ →tχ¯01 or t¯ →bχ¯±1 →bW(∗)χ¯01 , where χ¯01 (χ¯±1) denotes the lightest neutralino (chargino) in supersymmetric models. The search targets a fully-hadronic final state in events with four or more jets and large missing transverse momentum. No significant excess over the Standard Model background prediction is observed, and exclusion limits are reported in terms of the top squark and neutralino masses and as a function of the branching fraction of t¯ →tχ¯01 . For a branching fraction of 100%, top squark masses in the range 270–645 GeV are excluded for χ¯01 masses below 30 GeV. For a branching fraction of 50% to either t¯ →tχ¯01 or t¯ →bχ¯±1 , and assuming the χ¯±1 mass to be twice the χ¯01 mass, top squark masses in the range 250–550 GeV are excluded for χ¯01 masses below 60 GeV.